Comportamento Ecológicode Alunos Pós-Graduandosde uma Instituição Pública - Damiana Machado de Almeida (Universidade Regional do Noroeste do Estado do Rio Grande do Sul, 2015)
Understand the issues surrounding the topic environment is essential so that we can ensure futuregenerations the opportunity to take advantage of currently existing natural resources. These issues arefundamental to identify the factors that influence human behavior with regard to their relationship withthe environment. But the behavioral issues associated with the environment are still poorly studied.Thus, this research aims to investigate the ecological behaviors of students enrolled in the GraduateProgram of a public institution. For this, we used the methodology as descriptive research, quantitativeapproach and survey type. The instrument for the identification of environmental performance wasorganized from the Ecological Behavior Scale (ECE) Tamayo and Pato (2006). The research sampleconsisted of 70 respondents, in which it was possible to identify results that some activities of pro-environmental behavior are already part of the routine, mainly related to urban sanitation and energysaving. In contrast the ecological behaviors less adopted by graduate students are related to waterconservation and participation in volunteer work related to the environment. It is concluded that thereis need for greater public awareness researched with regard to ecological behaviors.